Recent Topics in Acoustic Scattering Coefficient Determination for Wall Surfaces. Issue 2 (June 2014) - Sakuma, Tetsuya; Lee, Hyojin
Three recent topics in acoustic scattering coefficient determination for wall surfaces are briefly presented: 1) validation of the reverberation room method of ISO 17497-1, 2) a new method of measuring normal-incidence coefficients, and 3) alternative determination by numerical simulation. First, the ISO method is reconsidered regarding unclear requirements of two approaches with stepwise and continuous rotation. It is theoretically and experimentally verified that the stepwise approach has a minimum number of angular steps, whereas the continuous approach has a minimum revolution period if using MLS signals, however if using swept sine signals, in the same way as the stepwise approach. Furthermore, the minimum requirements increase as the sample's scattering coefficient is higher, and unexpectedly, as the room's absorption area is smaller. Second, a new laboratory method is introduced for measuring normal-incidence coefficients, which would be useful to evaluate suppression of flutter echoes. The measurement is done in a rectangular room where installing highly absorbent materials on all vertical walls, and a test sample on the floor. In the one-dimensional field, normal-incidence coefficients of the sample can be determined by measuring the change in reverberation time with and without it. Third, as the alternative to measurement, numerical determination of scattering coefficients is demonstrated and further practical applications are discussed.